The grotesque character in César Vallejo’s «Cera» - Espinoza Espinoza, Esther (2023)
This study proposes the analysis of the aesthetic dimension of Chale, a character in the short story «Cera», from César Vallejo›s Escalas, based on the concept of the modern grotesque and one of its figures: the trickster. The character of the Chinese gambler, his marginality, his elaborate technique for mastering the dice as a representation of destiny, are also a metaphor for the artist in modernity. In this way, Vallejo reaffirms in Escalas his creative freedom.